Enhancing Students' Science Process Skills on Sound Waves Through Learning Cycle 7E Integrated with Phet - Lina Aviyanti; Della Merlinda; Amalia Weka Gani (Syntax Idea)
This study is prompted by the lack of science process skills among students in physics learning. Through the implementation of the Learning Cycle 7E integrated with PhET, this study aims to enhance students' science process skills on sound waves. A pre-experimental research design with one group pretest-posttest design was used, involving 30 students of grade XI in one of the high schools in Bandung. The instruments employed in this study comprise science process skills test, observation sheets on the implementation of learning model, and student response questionnaire. The paired sample t-test and N-Gain were used to assess the enhancement in students' science process skills. The findings revealed that the implementation of the Learning Cycle 7E integrated with PhET can enhance students' science process skills in the moderate category, with an N-gain score of 0.63. In addition, the paired sample t-test revealed significant differences in students' science process skills after engaging in classroom learning. The implementation of the Learning Cycle 7E integrated with PhET has shown the "very good" category, and received positive responses from students. This study has provided evidence that integrating the Learning Cycle 7E with PhET can improve students' science process skills on sound waves.